158 The 'forgotten' generation: quality of life in men living with duchenne muscular dystrophy. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Laidlaw, Sheonad; Carduff, Emma
Abstract : Background: Duchenne Muscular Dystrophy (DMD) is an x-linked, ultra-rare neuromuscular condition affecting 1 in 3600–6000 live male births. Life expectancy is increasing thanks to targeted intervention and advancing medical treatment. Longer survival and advancing age means a greater dependence on family, friends and the wider community, and increasing social and health care costs. However, little is known about quality of life (QoL) in adults with DMD. Aim: To investigate and explore quality of life in men living with DMD in the West of Scotland. Methods: This was a qualitative interview study using the 'Schedule for the Evaluation of Individual Quality of life – Direct Weighting' (SEIQoL-DW) tool, an interview based instrument which allows the assessment of elements that contribute to an individual's QoL. Men over the age of 25 and living in the West of Scotland were identified and recruited through the Scottish Muscle Network – a multidisciplinary clinical network. The interviews were transcribed and analysed thematically applying descriptive labels to the data. Results: Six men were recruited and interviewed. A number of themes were characterised as key to good QoL: strong personal relationships providing support and advocacy; meaningful connection with the world through hobbies and on-line communities; being in control of physical and mental well being, supported by knowledgeable and approachable health care professionals; continued independence through use of essential equipment both in and out of the adapted accessible home; and a positive, resilient attitude to life with a disability. Conclusions: Key improvements could improve QoL in this 'forgotten' group of adults: upskilling and support for all care givers; lifelong input from physiotherapy; timely access to psychological support; improved access to respite facilities; better co-ordinated holistic multidisciplinary care; and proactive advance care planning.